2010
DOI: 10.1002/bip.21577
|View full text |Cite
|
Sign up to set email alerts
|

A structurally driven analysis of thiol reactivity in mammalian albumins

Abstract: Understanding the structural basis of protein redox activity is still an open question. Hence, by using a structural genomics approach, different albumins have been chosen to correlate protein structural features with the corresponding reaction rates of thiol exchange between albumin and disulfide DTNB. Predicted structures of rat, porcine, and bovine albumins have been compared with the experimentally derived human albumin. High structural similarity among these four albumins can be observed, in spite of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…The differences between the two species suggest more interactions of E2072 with plasma albumins/proteins probably by formation of reversible proteinthiol-mixed disulfides in rodents compared with primates. Such species differences in plasma albumin reactivity have been described previously (Spiga et al, 2011). It is likely that both the homodisulfide and the mixed disulfides formed in vivo serve as a reversible depot of E2072 and help to maintain the monomer in circulation, which results in its prolonged pharmacological effects.…”
Section: Pharmacokinetics Of E2072 and Its Homodisulfidesupporting
confidence: 59%
“…The differences between the two species suggest more interactions of E2072 with plasma albumins/proteins probably by formation of reversible proteinthiol-mixed disulfides in rodents compared with primates. Such species differences in plasma albumin reactivity have been described previously (Spiga et al, 2011). It is likely that both the homodisulfide and the mixed disulfides formed in vivo serve as a reversible depot of E2072 and help to maintain the monomer in circulation, which results in its prolonged pharmacological effects.…”
Section: Pharmacokinetics Of E2072 and Its Homodisulfidesupporting
confidence: 59%
“…Fourth, not only the Cys34 thiol does ionize but also other neighboring residues do (e.g. Asp38, His39 and Tyr84) whose ionization states may affect the former [33,34]. In connection to this, it has been shown that Tyr84Phe and His39Leu mutations have a profound impact on Cys34 reactivity with DTNB, in a way not completely understood yet [33].…”
Section: Introductionmentioning
confidence: 92%
“…The dethiolation processes of XSSP of albumin [21,22] and the notions regarding the mechanisms of thiol exchange reactions [38] are useful for a better prediction of the processes of PSSP dethiolation.…”
Section: → Pssp)mentioning
confidence: 99%
“…On the contrary the reactions (2) and (3) express different thermodynamic tendencies that are identifiable on the basis of the leaving groups. These groups are those thiols that in thiol exchange reactions of XSSP and have the lowest pKa value [21,22], namely XSH in reactions (2) or (4), or PSH in reaction (3), respectively. Similar considerations can be used to predict the PSSP dethiolation via thiol exchange reactions.…”
Section: → Pssp)mentioning
confidence: 99%
See 1 more Smart Citation